A comparative study of Trypanosoma cruzi infection in sylvatic mammals from a protected and a disturbed area in the Argentine Chaco - Orozco, Maria Marcela (2016)
Understanding the complex epidemiology of Trypanosoma cruzi transmission cycles requires comparative studies in widely different environments. We assessed the occurrence of T. cruzi infection in sylvatic mammals, their infectiousness to the vector, and parasite genotypes in a protected area of the Argentine Chaco, and compared them with information obtained similarly in a nearby disturbed area. A total of 278 mammals from >23 species in the protected area were diagnosed for T. cruzi infection using xenodiagnosis, kDNA-PCR and nuclear satellite DNA-PCR (SAT) from blood samples. The relative abundance and species composition differed substantially between areas. Didelphis albiventris opossums were less abundant in the protected area; had a significantly lower body mass index, and a stage structure biased toward earlier stages. The capture of armadillos was lower in the protected area. The composite prevalence of T. cruzi infection across host species was significantly lower in the protected area (11.1%) than in the disturbed area (22.1%), and heterogeneous across species groups. The prevalence of infection in D. albiventris and Thylamys pusilla opossums was significantly lower in the protected area (nil for D. albiventris), whereas infection in sigmodontine rodents was three times higher in the protected area (17.5 versus 5.7%). Parasite isolates from the two xenodiagnosis-positive mammals (1 Dasypus novemcinctus and 1 Conepatus chinga) were typed as TcIII; both specimens were highly infectious to Triatoma infestans. Fat-tailed opossums, bats and rodents were kDNA-PCR-positive and xenodiagnosis-negative. Desmodus rotundus and Myotis bats were found infected with T. cruzi for the first time in the Gran Chaco.